RESPONSE OF THE VENTURE INSTRUMENTARY BETTING-STARTUP OF THE INVESTMENT IN THE GALOZES OF THE INNOVATIVE ENERGY POSTAGE - Паньків, Олег (Socio-economic relations in the digital society, 2019)
The theoretical and methodological principles of promising managerial decisions concerning the efficiency of attracting financial resources, as well as the initiation and direct creation of fundamentally new sources of funding for the development of energy-oriented start-ups are considered. The role and place of the sectors of innovative energy saving and alternative sources of power supply in a complex system of energy independence of the country is determined. The way and the main directions of research and development of models of solving the aforementioned problem are outlined. As part of the search for optimization solutions, it is suggested to use the principles of the existing statistical and mathematical apparatus, marketing achievements and achievements in network development that take place in the prediction-game (bookmaking and exchange) business. An analogue comparison of the principal models was carried out, during which the existing types of energy-oriented start-ups were determined and presented. A separate direction in the economic search is proposed, and its profile characteristics are corrugated. The type of model is typical for Ukrainian conditions. At the heart of the search and research, the author proposed a method of comparing strategies for attracting financial resources into a gaming business whose nature has a similar process in terms of mathematical research of operations. To solve the investigated problem, it is proposed to apply the property of the law of the emergence. The analysis is based on a concrete example of the functioning of the tender procedure, namely the organization of public procurement. On the principle of auction — competitive character «to decrease» with obligatory observance of the evidently — oriented requirements — the simulation model of the solution of the raised topic is considered. The purpose of the article is to consider and analyze the author’s proposal to focus on such an important phenomenon as the constant creation of the difference between the expected price and the final contractual price. The model of the solution is based on the systematic combination of this phenomenon and the administrative stimulation of implementation and implementation of exclusively energy-innovation projects. The combination of these two points is the basis of an optimization policy for the potential formation and maintenance of a state program to search and stimulate the sources of funding for power plants.